Agenda for change : action plan for the economy / edited by Bibek Debroy and Parth Shah - Rajiv Gandhi Institute for Contemporary Studies (New Delhi, 1998)
This book contains following topics: Securities Markets; Should Indian Securities Markets Service Retail Investors? ; Small Enterprises-Protection to Promotion; Labour Market Policy; Labour Markets; The Public Distribution System; Essential Commodities Act; Economic Reforms and poverty; New Education Policy: Choice and Competition; Liberalising Indian Agriculture; Import Liberalisation and Agriculture etc.
Keywords: India - Economic conditions - 1998